Comparing the analgesic safety and efficacy of Diclofenac sodium tablet vs transdermal Diclofenac on postoperative third molar Extraction pain, swelling and trismus - Fauziya Dastagir; Balamurugan R (DiscoverSys Inc., 2019)
Objective: To compare the analgesic efficacy of oral diclofenac sodium to diclofenac sodium transdermal patch in the management of postoperative pain, swelling and trismus following surgical removal of impacted mandibular third molars.Material and Methods: The total of 100 patients were randomly assigned to one of the two groups. Group I patients were medicated with oral diclofenac sodium 50 mg thrice daily for 3days. Group II patients had transdermal diclofenac sodium patches 100 mg placed once daily for 3 days after mandibular third molar surgery. All the patients were assessed for pain using a visual analogue scale, swelling with three point discrimination and trismus by measuring the inter-incisal distance on 2nd and 7th postoperatively days.Results: Patients in group II had less pain, swelling and trismus when compared with group I on 2nd and 7th postoperative days with statistical significance of p<0.05 respectively. Â Conclusion: Transdermal diclofenac patches provide an effective way in management of postoperative pain, swelling and trismus in patients of mandibular impactions with negligible side effects and good patient compliance.